Group Development in Speaking Classroom for Adult Learners - Sigara, Hasbi Noris (Journal of English Teaching, Literature, and Applied Linguistics, 2019)
Group Development is a term used to indicate the patterns in the way groups of people change over time and make decisions. The study of group developments can be useful in speaking classroom especially in observing adult learners’ behaviors. Furthermore, it is also beneficial in understanding the process of decision making in group behavior especially in regarding speaking ability as one of the measurements in knowing someone’s language proficiency. People tend to consider speaking as the most important skill that they can acquire and they can assess their progress in communication. This article discusses on how group development create interaction and behavior decision in speaking classroom for adult learners.